2009
DOI: 10.1152/ajpheart.00984.2008
|View full text |Cite
|
Sign up to set email alerts
|

Translocon closure to Ca2+ leak in proliferating vascular smooth muscle cells

Abstract: Amer MS, Li J, O'Regan DJ, Steele DS, Porter KE, Sivaprasadarao A, Beech DJ. Translocon closure to Ca 2ϩ leak in proliferating vascular smooth muscle cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0
1

Year Published

2011
2011
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 35 publications
2
24
0
1
Order By: Relevance
“…Using established procedures, calcium leakage was studied directly after thapsigargin addition as well as indirectly as a reduction in thapsigargin-induced leakage following puromycin pre-treatment. [2][3][4][5][6][7] Both analyses were carried out using untreated cells, cells treated with either one or both of the two SEC61A1-specific siRNAs, and with cells treated with the negative control siRNA. Compared to untreated cells and to cells treated with the negative control subsequent store operated calcium entry (SOCE) in the presence of extracellular calcium.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Using established procedures, calcium leakage was studied directly after thapsigargin addition as well as indirectly as a reduction in thapsigargin-induced leakage following puromycin pre-treatment. [2][3][4][5][6][7] Both analyses were carried out using untreated cells, cells treated with either one or both of the two SEC61A1-specific siRNAs, and with cells treated with the negative control siRNA. Compared to untreated cells and to cells treated with the negative control subsequent store operated calcium entry (SOCE) in the presence of extracellular calcium.…”
Section: Discussionmentioning
confidence: 99%
“…The drug thapsigargin inhibits SERCAs and, thereby, reveals the calcium leak pathway. [2][3][4][5][6][7] Leakage of Ca 2+ from the ER can be visualized as a reduction of Ca 2+ concentration in the ER by employing an ER calcium indicator, such as Mag-FURA-2, in digitonin-permeabilized cells. Alternatively, it can be visualized as an increase in the cytosolic Ca 2+ concentration by employing a cytosolic calcium indicator, such as FURA-2, in intact cells in the presence or absence of extracellular Ca 2+ .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The heterotrimeric Sec61 complex in the ER membrane provides an aqueous path for newly-synthesized polypeptides into the lumen of the ER. Recent work from various laboratories suggested that this heterotrimeric complex may also form transient Ca 2+ leak channels [2][3][4][5][6][7][8] . The key observation for this notion was that release of nascent polypeptides from the ribosome and Sec61 complex by puromycin leads to transient release of Ca 2+ from the ER.…”
Section: Introductionmentioning
confidence: 99%